Predicting Factors of Suicidal Behavior among Early Adults - Inpun, Kamonpatch; Skulphan, Sombat; Thapinta, Darawan (Journal of Phrapokklao Nursing College, Chanthaburi, 2026)
This predictive correlational descriptive research aimed to explore suicidal behavior and factors predicting suicidal behavior among early adults. The participants were 89 early adults who had received services from mental health and psychiatric outpatient departments at community hospitals in Chiang Mai, Lampang, and Phrae Province. The research instruments included the demographic data record, the Rosenberg Self-Esteem Scale: Revised Thai RSES with a reliability of .80, the social support questionnaire with a reliability of .80, the revised version of the Thai Herth Hope Index with a reliability of .80, and the Mini International Neuropsychiatric Structure Interview (M.I.N.I.): Suicidality part with a reliability of 1. Data were collected from March to May 2021. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results revealed that most early adults were at a low level of suicide risk (79.77%). Social support is the only factor that could statistically significantly predict suicidal behavior among early adults, accounting for 33.90% of the variance (R2 = .339, p < .01). This research suggests that psychiatric nurses should enhance systemic social support for their clients to prevent suicidal behavior.